2023
DOI: 10.1167/tvst.12.4.3
|View full text |Cite
|
Sign up to set email alerts
|

Normalized Blood Flow Index in Optical Coherence Tomography Angiography Provides a Sensitive Biomarker of Early Diabetic Retinopathy

Abstract: Purpose To evaluate the sensitivity of normalized blood flow index (NBFI) for detecting early diabetic retinopathy (DR). Methods Optical coherence tomography angiography (OCTA) images of healthy controls, diabetic patients without DR (NoDR), and patients with mild nonproliferative DR (NPDR) were analyzed in this study. The OCTA images were centered on the fovea and covered a 6 mm × 6 mm area. Enface projections of the superficial vascular plexus (SVP) and the deep capil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…OCTA is label-free and thus is completely non-invasive, compared to traditional fluorescein angiography. Studies have shown that OCTA provides improved capability for detecting subtle vascular distortions associated with the progression of retinal pathology, such as vessel dropout, foveal abnormalities, and increased vessel tortuosity 1 , 2 . Studies demonstrate that OCTA could even detect microaneurysms that were undetected on dilated clinical examination 3 .…”
Section: Introductionmentioning
confidence: 99%
“…OCTA is label-free and thus is completely non-invasive, compared to traditional fluorescein angiography. Studies have shown that OCTA provides improved capability for detecting subtle vascular distortions associated with the progression of retinal pathology, such as vessel dropout, foveal abnormalities, and increased vessel tortuosity 1 , 2 . Studies demonstrate that OCTA could even detect microaneurysms that were undetected on dilated clinical examination 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has focused on quantitative analysis of OCTA images for the objective detection and classification of retinal diseases [12][13][14][15][16][17][18][19][20][21][22][23]. Previous work by Alam et al [24] and Son et al [25] leveraged en face OCT and en face OCTA features for AV segmentation through quantitative feature analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has focused on quantitative analysis of OCTA images for the objective detection and classification of retinal diseases [12][13][14][15][16][17][18][19][20][21][22][23]. Previous work by Alam et al [24] and Son et al [25] leveraged en face OCT and en face OCTA features for AV segmentation through quantitative feature analysis.…”
Section: Introductionmentioning
confidence: 99%